2015
DOI: 10.1001/jamaneurol.2015.1444
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Acetylcholine Receptor Antibody Testing in Ocular Myasthenia Gravis

Abstract: The sensitivity of acetylcholine receptor (AChR) antibody testing is thought to be lower in ocular myasthenia gravis (OMG) compared with generalized disease, although estimates in small-scale studies vary. There is little information in the literature about the implications of AChR antibody levels and progression from OMG to generalized myasthenia gravis.OBJECTIVES To test the hypothesis that serum AChR antibody testing is more sensitive in OMG than previously reported and to examine the association between AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 14 publications
8
64
2
3
Order By: Relevance
“…The main finding in this study is the low conversion rate of OMG to GMG in an Asian population, estimated at 7.7% at 2 years of follow‐up after diagnosis and at 10.6% at median follow‐up of 40.8 months. This is in contrast to earlier findings in Caucasians, which varied from 50% to 20%–31% . It is possible that the genetic background of Asians explains the lower conversion rate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The main finding in this study is the low conversion rate of OMG to GMG in an Asian population, estimated at 7.7% at 2 years of follow‐up after diagnosis and at 10.6% at median follow‐up of 40.8 months. This is in contrast to earlier findings in Caucasians, which varied from 50% to 20%–31% . It is possible that the genetic background of Asians explains the lower conversion rate.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to earlier findings in Caucasians, which varied from 50% 19 to 20%-31%. 3,6,8,20 It is possible that the genetic background of Asians explains the lower conversion rate. However, alternative explanations may also exist, including false OMG diagnoses and/or role of immunosuppression in reducing the conversion rate.…”
Section: Discussionmentioning
confidence: 99%
“…The binding antibody is highly specific but is thought to be less sensitive in OMG compared to generalized disease [17]. However, in the study conducted by Peeler et al, a higher sensitivity of AChR antibody was demonstrated in OMG patients in the rate of 70.9% [18]. The authors suggested that older age, male sex and progression to generalized disease were significantly associated with a positive antibody result.…”
Section: Diagnostic Testingmentioning
confidence: 95%
“…Previous reports showed a trend toward frequent progression to generalized form of MG in older individuals [10]. In addition, high AChR antibody titers at presentation have been found to be associated with increased risk of generalization [11]. Previous studies showed increased risk of conversion with thymoma [12], while there is some evidence in the literature showing thymectomy to be effective in controlling juvenile OMG by reducing the risk of generalization [13].…”
Section: Factors Affecting Conversion Ratesmentioning
confidence: 99%
“…Yet, these tests can overlook patients with pure ocular myasthenia gravis (2). Standard laboratory assays for acetylcholine receptor antibody levels are often negative (3,4). Tensilon testing, which some physicians are reluctant to perform, lacks sufficient sensitivity to identify many patients (5).…”
mentioning
confidence: 99%